Development of a digital twin model for electric bikes based on urban experimental driving in full electric mode - Genc, Mehmet Onur (Korean Soc Mechanical Engineers, 2023)
In this study, E-bike, called pedelec due to being driven via a pedal and electric excitation is investigated experimentally based on energy consumption at defined urban road profiles under full electrical mode without pedal usage. The digital twin (DT) model is created based on the powertrain system model to estimate the consumed instant electrical power dependend on voltage, current, torque, and road type classifications. To achieve these targets, a data logging system is designed and programmed to measure consumed electrical power as current and voltage inputs. Road profiles are divided into the asphalt and graded gravel at different slope levels. As next step, the obtained energy consumption data is used in powertrain modeling to create physical E-bike model, which is the input for neural network model representing the DT model. This novel test methodology provides the approaches of energy consumption and driving range calculation in E-bike powertrain system modelling.
Keywords: Electric bicycle; Hub motor; System modeling; Powertrain; Electro mobility; Digital twin